2001
DOI: 10.1046/j.1439-0272.2001.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the acrosome reaction in human spermatozoa: comparison of cytochemical and fluorescence techniques

Abstract: The acrosome reaction, which is essential for fertilization, includes fusion and vesiculation of the plasma membrane with the outer acrosomal membrane of spermatozoa, thereby releasing the acrosomal content. Determination of the ability of spermatozoa to undergo the acrosome reaction has proved to be a useful parameter in evaluation of infertile patients. The objective of this study was to compare cytochemical techniques, such as double stain (Giemsa/trypan blue) and triple stain (Bismarck brown/rose bengal/tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In agreement with our results, Way et al (1995) observed lower percentages of sperm with detached acrosome as well as viable sperm in ejaculated bovine sperm stained with Trypan blue and Giemsa stain, as opposed to samples subjected to FITC-PSA labelling. The results of the present experiments are consistent with the data obtained by Risopatrón et al (2001) on human spermatozoa. In our experiments (Table 1) no significant differences (P > 0.05) were detected in the frequency of acrosome-reacted sperm either by double staining (37.98%) or by FITC-PSA labelling (39.33%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, Way et al (1995) observed lower percentages of sperm with detached acrosome as well as viable sperm in ejaculated bovine sperm stained with Trypan blue and Giemsa stain, as opposed to samples subjected to FITC-PSA labelling. The results of the present experiments are consistent with the data obtained by Risopatrón et al (2001) on human spermatozoa. In our experiments (Table 1) no significant differences (P > 0.05) were detected in the frequency of acrosome-reacted sperm either by double staining (37.98%) or by FITC-PSA labelling (39.33%).…”
Section: Resultssupporting
confidence: 93%
“…Two methods [double staining and Hoechst/FITC-Pisum sativum agglutinin (PSA) labelling] are commonly used for evaluating the acrosome reaction, but contradictory data have been obtained by these techniques. Risopatrón et al (2001) reported a decrease in the number of live and acrosome-reacted human spermatozoa after double staining in comparison with the FITC-PSA method in humans. In contrast, Kőhn et al (1997) found comparable results of viability as well as acrosome reaction rate with human sperm.…”
mentioning
confidence: 99%
“…The spermatozoa were stained by 0.8% of Bismarck brown Y (B-2759, Sigma-Aldrich) for 10 min at 40°C, followed by washing with distilled water. Finally, they were incubated in 0.8% rose bengal 0.1 M Tris (R-3877, Sigma-Aldrich) for 40 min at RT, washed in distilled water, dehydrated in alcohol gradients (50%, 70%, 96%), and mounted with a coverslip [18]. Following staining, the intact acrosome showed a pink acrosomal region, while the white acrosomal region was a sign of degeneration.…”
Section: Sperm Chromatin Dispersion (Scd)mentioning
confidence: 99%
“…It should be noted that induction of the acrosome reaction does not result in the complete simultaneous removal of the acrosome from all such treated sperm cells, and that some cells display intermediate PSA-FITC levels. Sperm cells showing more than two-thirds of the acrosome without fluorescence or with a fluorescing band at the equatorial segment were considered to be AR (Risopatro ´n et al, 2001). A bandlike pattern was detected at the equatorial zone for the PATE and PATE-M proteins in both the AR and the AI sperm cells, whereas this pattern was seen at the post-acrosomal region for the PATE-B protein.…”
Section: Localization Of Pate-like Proteins On Ejaculated Sperm Cellsmentioning
confidence: 99%